2020
DOI: 10.1177/1938640020950119
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity After Metal Allergy to a Total Ankle Implant

Abstract: Metal allergy to total ankle arthroplasty is rare but can be both an unpredictable and devastating complication. Current literature describing metal allergy in orthopaedics is limited with there being no report to date on metal allergy after total ankle arthroplasty. Our patient underwent a total ankle arthroplasty and developed a diffuse rash 7 weeks postoperatively. The patient then tested positive for a metal allergy and ultimately was converted to an arthrodesis. In the setting of postoperative pain, swell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Наприклад, залізо є необхідним компонентом гемоглобіну в еритроцитах, кобальт входить до складу вітаміну B 12 , тому без цих металів організм не може виробляти еритроцити. Цинк та мідь беруть участь у процесах метаболізму, а дефіцит будь-якого з них може призвести до розвитку анемії [6]. Водночас ці та інші метали, попадаючи в організм людини у великій кількості, можуть викликати тяжкі хвороби, у тому числі і алергію.…”
Section: вступunclassified
“…Наприклад, залізо є необхідним компонентом гемоглобіну в еритроцитах, кобальт входить до складу вітаміну B 12 , тому без цих металів організм не може виробляти еритроцити. Цинк та мідь беруть участь у процесах метаболізму, а дефіцит будь-якого з них може призвести до розвитку анемії [6]. Водночас ці та інші метали, попадаючи в організм людини у великій кількості, можуть викликати тяжкі хвороби, у тому числі і алергію.…”
Section: вступunclassified
“…26 There is a case report of a TAR patient with a severe metal allergy necessitating implant removal and conversion to fusion. 29 In addition, a study of ankle fusion patients with workers' compensation reported significantly lower American Orthopaedic Foot & Ankle Society scores and higher pain scores postoperatively. 28 However, most of these potential causes are extrapolated from the total hip/ knee replacement population and have not been well described in the TAR literature.…”
Section: Is It Something Unique/rare?mentioning
confidence: 99%